1986
DOI: 10.1126/science.3726531
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Rapid Effect of 17β-Estradiol on Medial Amygdala Neurons

Abstract: The mechanism by which sex steroids rapidly modulate the excitability of neurons was investigated by intracellular recording of neurons in rat medial amygdala brain slices. Brief hyperpolarization and increased potassium conductance were produced by 17 beta-estradiol. This effect persisted after elimination of synaptic input and after suppression of protein synthesis. Thus, 17 beta-estradiol directly changes the ionic conductance of the postsynaptic membrane of medial amygdala neurons. In addition, a greater p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
116
0
3

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(122 citation statements)
references
References 24 publications
3
116
0
3
Order By: Relevance
“…The ovary in several species releases Ca2+ from intracellular stores within seconds of E, exposure, perhaps via a "nonclassical" receptor (Morley et al, 1992). In another population of guinea pig hypothalamic neurons, E, directly modulates a potassium conductance, possibly via modulation of intracellular nucleotides (Kelly et al, 1984;Nabekura et al, 1986;Minami et al, 1990). A similar effect was seen in some neurons in the present study, but there was no decrease in DAMGO potency in any of these neurons following E, application (n = 8).…”
Section: Potential Mechanisms Of E Actionsupporting
confidence: 58%
“…The ovary in several species releases Ca2+ from intracellular stores within seconds of E, exposure, perhaps via a "nonclassical" receptor (Morley et al, 1992). In another population of guinea pig hypothalamic neurons, E, directly modulates a potassium conductance, possibly via modulation of intracellular nucleotides (Kelly et al, 1984;Nabekura et al, 1986;Minami et al, 1990). A similar effect was seen in some neurons in the present study, but there was no decrease in DAMGO potency in any of these neurons following E, application (n = 8).…”
Section: Potential Mechanisms Of E Actionsupporting
confidence: 58%
“…Using intracellular recording techniques, it was found that fast perfusion of estrogen (100 pM) hyperpolarized arcuate neurons within seconds in a hypothalamic slice preparation and that this effect was reversed within minutes of washing out estrogen (Kelly et al, 1980). Similar actions of E2 were also demonstrated in hypothalamic ventromedial nucleus (VMH) and amygdala neurons, even in the presence of protein synthesis inhibitors (Nabekura et al, 1986, Minami et al, 1990. Later, it was found that GnRH neurons, identified post hoc using a combination of intracellular dye labeling and immunocytochemical staining, were a target of estrogen actions (Kelly et al, 1984).…”
mentioning
confidence: 86%
“…In contrast, estrogen has also been found to produce short-term actions on the electrical properties of neurons and transmitter release. The rapid onset and time course of these effects suggest that they are distinct from the genomic mechanism of action and indicate that estrogen may act on membrane recep-tors or other cellular components to alter neuronal events (Nabekura et al, 1986;Smith et al, 1987Smith et al, , 1989Minami et al, 1990;Kelly et al, 1992;Majewska, 1992;Paul and Purdy, 1992). However, the mechanisms to account for the rapid actions of estrogen have remained elusive.…”
mentioning
confidence: 97%